Challenges in the employability of halal studies graduates in Malaysia - Ibrahim, Muhammad Irhammudin; Jamaludin, Mohammad Aizat; Muflih, Betania Kartika; Hashim, Yumi Zuhanis Has-Yun (Halalan Thayyiban Research Centre, Universiti Islam Sultan Sharif Ali (UNISSA), 2024)
The expansion of the halal business in Malaysia has resulted in a rising need for individuals who possess specialized qualifications in halal studies. Nevertheless, despite the growing market, these graduates encounter substantial obstacles in terms of their employability. This study examines the elements that influence the employability of halal studies graduates in Malaysia. It focuses on the important concerns connected to the relevance of the curriculum, recognition from the industry, inadequacies in infrastructure, and the competence of instructors. The study utilizes a qualitative research methodology, incorporating data from both primary and secondary sources, to offer a thorough examination of the halal education ecosystem. The results suggest that the absence of a uniform curriculum, inadequate infrastructure, and limited involvement of the sector impede the successful training of graduates for the halal employment market. Moreover, the discrepancy between academic education and the requirement of halal industry sector worsens the difficulties in finding employment. The paper suggests fostering stronger collaboration between educational institutions and industry stakeholders, implementing curriculum reforms, and establishing accreditation standards as measures to enhance the employability of halal studies graduates and promote the sustainable expansion of the halal industry in Malaysia.